1999
DOI: 10.1007/s002130050906
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to nicotine enhances acquisition of ethanol drinking by laboratory rats in a limited access paradigm

Abstract: Observations in humans suggest that the initial use of tobacco occurs in close temporal proximity to experimentation with alcohol. There have been relatively few research reports, however, examining possible interactions between these two agents. The present experiments examined the effect of nicotine exposure on the acquisition of ethanol drinking behavior in a limited access procedure. In experiment 1, rats were presented with 1-h access to ethanol solutions of increasing concentration for a period of 20 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
64
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 20 publications
14
64
2
Order By: Relevance
“…However, nicotine pre-treatment did not affect the consummatory aspects when animals were allowed to freely intake ethanol for 24 hours. Nicotine pre-treatment has previously shown to increase alcohol seeking in adult rodents [13,[31][32][33][34]. In accordance with our results, López-Moreno et al [35] showed an increase in ethanol selfadministration 14 days after cessation of chronic nicotine administration in adult rats.…”
Section: Discussionsupporting
confidence: 92%
“…However, nicotine pre-treatment did not affect the consummatory aspects when animals were allowed to freely intake ethanol for 24 hours. Nicotine pre-treatment has previously shown to increase alcohol seeking in adult rodents [13,[31][32][33][34]. In accordance with our results, López-Moreno et al [35] showed an increase in ethanol selfadministration 14 days after cessation of chronic nicotine administration in adult rats.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, this was also reported for nicotine exposure on ethanol drinking in rats [20]. Thus, it would be tempting to speculate as to whether the intake of one of these substances is a primary process effecting the other consumptions.…”
Section: Discussionsupporting
confidence: 66%
“…Recently, several animal studies on the interaction of tobacco and alcohol have been published. The findings of these studies appear to support the observation that levels of ethanol intake in rats injected with nicotine are significantly elevated [17][18][19][20].…”
Section: Introductionsupporting
confidence: 77%
“…For example, in the brain stimulation reward model, both drugs decrease the dose of nicotine required to lower the self-stimulation threshold (Huston-Lyons et al 1993). Conversely, prior exposure to nicotine enhances the conditioned rewarding effects of morphine (Shippenberg et al 1996), accelerates the acquisition of ethanol drinking behavior in naive rats (Smith et al 1999) and predisposes rats to self-administer a low dose of cocaine (Horger et al 1992). In the place preference paradigm, nicotine can potentiate the action of low doses of cocaine, whereas antagonism of nAChRs decreases the response to a threshold dose of cocaine ).…”
Section: Nicotine Reinforcement and Withdrawalmentioning
confidence: 99%